2017
DOI: 10.1016/j.cyto.2017.06.017
|View full text |Cite
|
Sign up to set email alerts
|

IL-33 and the intestine: The good, the bad, and the inflammatory

Abstract: Interleukin-33 (IL-33) is a member of the IL-1 cytokine family that has been widely studied since its discovery in 2005 for its dichotomous functions in homeostasis and inflammation. IL-33, along with its receptor suppression of tumorigenicity 2 (ST2), has been shown to modulate both the innate and adaptive immune system. Originally, the IL-33/ST2 signaling axis was studied in the context of inducing type 2 immune responses with the expression of ST2 by T helper 2 (TH2) cells. However, the role of IL-33 is not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
75
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 133 publications
(225 reference statements)
3
75
0
2
Order By: Relevance
“…Loss‐of‐function mutations in IL‐33 in allergic patients as well as in IL‐1R4 were identified, supporting the findings in genome‐wide association studies that identified the IL‐33/IL‐1R4 pathway as the most relevant factor in allergy . Besides allergic asthma, increased levels of IL‐33 have been found in many disorders associated with acute or chronic inflammation (reviewed in ) such as in the intestine (reviewed in ) and arthritis.…”
Section: Focus On the Il‐1r Familymentioning
confidence: 99%
“…Loss‐of‐function mutations in IL‐33 in allergic patients as well as in IL‐1R4 were identified, supporting the findings in genome‐wide association studies that identified the IL‐33/IL‐1R4 pathway as the most relevant factor in allergy . Besides allergic asthma, increased levels of IL‐33 have been found in many disorders associated with acute or chronic inflammation (reviewed in ) such as in the intestine (reviewed in ) and arthritis.…”
Section: Focus On the Il‐1r Familymentioning
confidence: 99%
“…Interleukin‐33 functions both as a cytokine and as a nuclear transcription factor . It activates both the innate and adaptive immune system and is a critical cytokine for Th2‐mediated host defense, as well as playing a key role in regulating immune responses in barrier tissues such as the intestine . Interleukin‐33 also functions as an alarmin and is released by epithelial and endothelial cells in response to cell injury and necrosis .…”
Section: Discussionmentioning
confidence: 99%
“…Also, because IL‐33 promotes an early Th2 immune response, it helps to regulate Th1 immune responses and prevent autoimmunity . Interleukin‐33 has been shown to influence both T regulatory cells and Th17 cells to decrease inflammation and protect the intestinal mucosa from self‐inflicted injury . Studies suggest that nuclear IL‐33 can sequester nuclear factor kappa‐light‐chain‐enhancer of activated B cells (NF‐κB), thereby decreasing subsequent NF‐κB‐generated proinflammatory signaling .…”
Section: Discussionmentioning
confidence: 99%
“…The IL-33/ST2 axis is important for the maintenance of the epithelial integrity of the gastrointestinal tract [57]. Similar to its roles in the cardiovascular and central nervous system, IL-33 plays both beneficial and pathological roles in gastrointestinal diseases [57].…”
Section: Gastrointestinal Diseasesmentioning
confidence: 99%
“…Similar to its roles in the cardiovascular and central nervous system, IL-33 plays both beneficial and pathological roles in gastrointestinal diseases [57]. In mouse models of experimental colitis induced by dextran sulphate sodium (DSS) or trinitrobenzene sulfonic acid (TNBS), deficiency of the IL33 or IL1RL1 genes leads to amelioration of the disease, compared to its outcome in wild-type control mice, and treatment with an ST2 blocking antibody ameliorates experimental colitis by enhancing mucosal healing in mice [58].…”
Section: Gastrointestinal Diseasesmentioning
confidence: 99%